Habitat‐driven population structure of bottlenose dolphins, Tursiops truncatus, in the North‐East Atlantic. Issue 4 (February 2014) - Louis, Marie; Viricel, Amélia; Lucas, Tamara; Peltier, Hélène; Alfonsi, Eric; Berrow, Simon; Brownlow, Andrew; Covelo, Pablo; Dabin, Willy; Deaville, Rob; de, Renaud; Gally, François; et al.
Abstract Despite no obvious barrier to gene flow, historical environmental processes and ecological specializations can lead to genetic differentiation in highly mobile animals. Ecotypes emerged in several large mammal species as a result of niche specializations and/or social organization. In the North‐West Atlantic, two distinct bottlenose dolphin (Tursiops truncatus) ecotypes (i.e. 'coastal' and 'pelagic') have been identified. Here, we investigated the genetic population structure of North‐East Atlantic (NEA) bottlenose dolphins on a large scale through the analysis of 381 biopsy‐sampled or stranded animals using 25 microsatellites and a 682‐bp portion of the mitochondrial control region. We shed light on the likely origin of stranded animals using a carcass drift prediction model. We showed, for the first time, that coastal and pelagic bottlenose dolphins were highly differentiated in the NEA. Finer‐scale population structure was found within the two groups. We suggest that distinct founding events followed by parallel adaptation may have occurred independently from a large Atlantic pelagic population in the two sides of the basin. Divergence could be maintained by philopatry possibly as a result of foraging specializations and social organization. As coastal environments are under increasing anthropogenic pressures, small and isolated populations might be at risk and require appropriate conservation policies to preserve their habitats. While genetics can be a powerful first step to delineate ecotypes in protected and difficult to access taxa, ecotype distinction should be further documented through diet studies and the examination of cranial skull features associated with feeding.